ANALISI FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN ORGANISASI DALAM PENERAPAN E-COMMERCE - Adhitya Yoga Prasetya (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
E-commerce has been giving a lot of benefits to small andmedium enterprises (SMEs), but there are only a few SMEs whichhave adopted it. Therefore, it is necessary to find out what are thefactors that support SMEs to adopt E-commerce. So far, researcheson E-commerce have been done on foreign-large-scale businesses,while researches on SMEs especially about the adoption of E-commerce have been a few. That is why this research will discussthe adoption of E-commerce on Indonesian SMEs and will includethe factors that support E-commerce adoption. The problems in thisresearch are elaborated into research questions, i.e. do, topmanagement support, organizational readiness, external pressure,and perceived benefits have significant positive effect to E-commerce adoption? And does the adoption have significantpositive effect to company’s performance? The purpose of thisresearch is to analyze factors that support E-commerce adoption onIndonesian SMEs and to analyze whether the adoption improves theperformance of the SMEs. This technique is chosen because it is thesecond generation of multivariate analyzing technique that enablesresearchers to test the relation between complex variables to get anoverall view of the whole model. Besides, SEM can also test a seriesof a complicated relation simultaneously. The results of thisresearch explain that top management support, organizationalreadiness, external pressure, and perceived benefits haveSignificant positive effect to E-commerce adoption, and theadoption have significant positive effect to company’s performance.